ANALISIS POLA SEBARAN LEMBAGA KESEJAHTERAAN SOSIAL ANAK (LKSA) KOTA MAKASSAR DENGAN MENGGUNAKAN METODE NEAREST NEIGHBORD - Mat Rasul; Putri Aprianti; Ester Meri; Maddatuang Maddatuang; Rahma Musyawarah (Jurnal Geografi, 2026)
The problem of children's social welfare, especially orphans and abandoned children, is a major concern in Makassar City, where many children face various challenges in meeting their basic needs. This study aims to analyze the distribution pattern of Child Social Welfare Institutions (LKSA) in Makassar City using spatial analysis on ArcGIS software tools in the Average Nearest Neighbor tool. The method used in the study is descriptive quantitative with a spatial approach. The data used is secondary data obtained from the Geospatial Information Agency and One Data Indonesia Makassar City for 2023-2024 related to LKSA data and verified through field observation to ensure the location of the LKSA is in accordance with the location in the field. The results of the analysis showed that the distribution of LKSA in Makassar City tended to be clustered with a Nearest Neighbor Ratio (NNR) value of 0.766, Z-Score -4.22, and a p-value of 0.000024. This inequality is influenced by several factors such as social dynamics, accessibility and economy. These findings indicate that there is an uneven distribution of LKSA that needs to be considered by the government and the community. The recommendation in this study is to emphasize the need to equitably distribute LKSA in several sub-districts that do not yet exist and still lack LKSA to ensure the fulfillment of the rights, welfare, and safety of children who need social protection.